Evaluation of a community-based One Health intervention to reduce the risk of Lyme disease in a high-incidence municipality - Liliana Potes; Catherine Bouchard; Jean-Philippe Rocheleau; Lucie Richard; Patrick Leighton; Jérôme Pelletier; Geneviève Baron; Cécile Aenishaenslin (CABI, 2023)
Abstract Integrated interventions coherent with the One Health approach are required to maximize the effectiveness of tick-borne disease prevention. The objective of this study was to evaluate the feasibility of a community-based One Health preventive intervention in a municipality reporting a high incidence of Lyme disease (LD) in the province of Quebec, Canada. The intervention integrated several activities to promote the adoption of preventive behaviours in the community (community component), with the reduction of infected ticks in the environment (environmental component). To evaluate short-term effects of the community component, quantitative data on knowledge, attitudes, and practices (KAP) of citizens were collected using online questionnaires at the beginning of the intervention and 1 year later. To evaluate the implementation of the intervention, a qualitative approach was principally used, and individual interviews (n=37) were conducted with key informants. Results showed that having a high level of participation in the community activities included in the intervention was associated with a higher adoption of preventive measures at the end of the intervention, although participation was not significantly associated with changes in KAP over the intervention period. Interviews revealed that the community mobilization approach was perceived as an effective and sustainable way to empower citizens and researchers with regard to LD prevention. This study suggests that community-based interventions of this type offer a promising approach to the prevention of tick-borne diseases.